ANALYTIC HIERARCHY PROCESS FOR SUPPLIER EVALUATION IN PROCUREMENT AND SUPPLY CHAINS - Shahraki, Alireza; Meysam, Kazemi E; Banihashemi, Seyyed Ali (International Journal of Management and Allied Research (IJMAR), 2024)
In the evolving landscape of industrial and service sectors, the focus has shifted towards optimizing outputs and analyzing the intricate dynamics of the supply chain’s upper and lower components. This paradigm shift underscores the realization among industrial and service units in developed countries that sustained profitability lies in achieving a harmonious and efficient integration of components within the supply chain. The traditional approach of supplier selection based solely on recommended prices has proven inadequate. In this complex environment, managers grapple with various factors such as opportunities, threats, competitor evaluation, and the delicate balance between quality and price. This paper delves into the multifaceted challenges faced by contemporary businesses in navigating the complexities of supply chain management and underscores the imperative of holistic strategies for sustained success.